How Do Firms Become Different? A Dynamic Model - Selove, Matthew (Management Science, 2014)
This paper presents a dynamic investment game in which firms that are initially identical develop assets that are specialized to different market segments. The model assumes that there are increasing returns to investment in a segment, for example, as a result of word-of-mouth or learning curve effects. I derive three key results: (1) Under certain conditions there is a unique equilibrium in which firms that are only slightly different focus all of their investment in different segments, causing small random differences to expand into large permanent differences. (2) If, on the other hand, sufficiently large random shocks are possible, firms over time repeatedly change their strategies, switching focus from one segment to another. (3) A firm might want to reduce its own assets in the smaller segment in order to entice its competitor to shift focus to this segment. This paper was accepted by J. Miguel Villas-Boas, marketing.